Development by Apply Problem Based Learning Models to Increase Students Creativity of State Vocational High School 1 Cerme - Satriawati, Asti; Nurlaela, Luthfiyah; Munoto, Munoto; Rijanto, Tri (Universitas Malikussaleh, 2020)
This study is a research on the development of devices in basic culinary subjects by applying a problem based learning models to increase students’ creativity, consisting of: 1) analysis the validity of the device, 2) analysis the practicality of the device, and 3) analysis the effectiveness of the device. This research was conducted in three stages of the 4-D model, which are defined, design, and develop. A device that have been developed will be tested in 10th Culinary Art 1 and 10th Culinary Art 2 grade of state vocational high school 1 Cerme in even semester of academic year 2019/2020 with by using a research design of One Group Pre-test Post-test Design Learning tools developed include: syllabus, lesson plans scenario, student book, worksheet and key worksheet, affective (social skills), affective (character behavior), cognitive (product), cognitive (process), cognitive (scientific creativity), and psikomotor. The results showed that (a) learning tools that are developed are valid, (b) the learning process runs well, (c) student creativity learning outcomes produce an increase in the high category.